PLoS Genetics Issue Image | Vol. 16(11) November 2020 (PLOS Genetics, 2020)
Meiosis and sex chromosome evolutionThe early stages of sex chromosome evolution are notoriously difficult to study. The meiotic behavior of neo-sex chromosomes reveals how some of the first steps of this evolution can be achieved and how they may even depend on the special requirements of meiosis. The image shows a diplotene spermatocyte of the African pygmy mouse Mus minutoides immunolabeled for protein SYCP3 (green), centromeres (pink) and histone γH2AX (blue). See Gil-Fernández et al. Download November's cover page.Image Credit: Ana Gil-Fernández and Jesús Page.